The Challenges and Considerations with Autologous Rib Microtia Reconstruction - Liu, Yi-Chun C.; Mukerji, Shraddha; Truong, Mai Thy (Facial Plastic Surgery, 2025)
Microtia encompasses a spectrum of congenital pinna malformation. Autologous rib reconstruction is a widely utilized surgical reconstruction technique for microtia. The surgery presents various challenges that can impact surgical outcomes and patient satisfaction. Sculpting and shaping the cartilage into a detailed auricular framework poses is a technically difficult surgery due to the complexity of the ear's anatomy. Postoperative complications such as scar formation, infection, and framework resorption may lead to poor aesthetic outcomes like asymmetry of the reconstructed ear and inadequate projection. Patient-related factors, such as age, rib cartilage quality and quantity, and psychological expectations, also play critical roles in determining success. Additionally, the surgeon's experience and expertise heavily influence the reconstruction's quality.This paper explores the challenges microtia surgeons face during the reconstruction process, emphasizing technical, patient-specific, and postoperative challenges. It underscores the importance of comprehensive preoperative planning, advanced surgical training, and ongoing research to mitigate these challenges and optimize outcomes in autologous rib microtia reconstruction.
Keywords: microtia; autologous rib microtia reconstruction; auricular reconstruction; microtia surgery